Board of Directors’ Responsibility for Activities of A Limited Liability which Having No Legal Entity Status - I Nyoman Sujana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The aim of this study is to find and analyzes the responsibility of Board of Directors of a Limited Liability Company (PT) operated the company and entered into legal relationship with third parties on behalf of the company when the company has not legally obtained the status of a legal entity. The focus study since business practice is always encountered with competition among entrepreneurs in the effort to gain profit in various unhealthy ways, thus it results in violations of laws and regulations. The research method was used was a normative legal study with a statutory, conceptual and analytical approach. The results of the study show that legal actions on behalf of the Company that has not obtained the status of a legal entity may only be carried out by all members of the Board of Directors together with the founders and members of Board of Commissioners of the Company. The novelty showed that every company need responsible for the company's damages or losses suffered by third parties having legal relationship with the company. Included for unlimited and mutual responsibility (jointly and severally). The actions of board of directors having exceeded their authority specified in the articles of association of the company, resulting in losses for the company shall not be considered as an action of the company. This loss will be the full responsibility of Board of Directors, as the limited liability company will turn into an unlimited liability.